The collected writings of J.N. Darby ; v.8 - Darby, John Nelson, 1800-1882; Kelly, William, 1821-1906 (Kingston-on-Thames, UK Stow Hill Bible and Tract Depot, 1957)
Contents : v. 8 : Prophetic no. 3
Brethren writer.
Keywords: Bible -- Brethren theology; Brethren movement -- historical writings